Rehabilitation of children with muscle-skeleton disorders - Polevoy, Georgiy (Bangladesh Journal of Medical Science, 2025)
Objectives Is to improve the function of the arch of the foot in primary school children who have flat feet by means of adaptive physical rehabilitation during classes using sets of physical exercises. Methods The study was conducted during the school year at a comprehensive school in Russia. The pedagogical experiment involved 88 elementary school children who are diagnosed with flat feet. All physical education classes were held according to the school schedule twice a week for 40 minutes. The control group studied according to the regular school physical education program, and the experimental group studied according to the experimental program, which included combined developing exercises, special exercises for corrective purposes for the arch of the foot, and outdoor games. Flat feet in children were determined using the Friedland index, jumping ability and fast muscle strength of legs were determined by the long jump, and muscle strength of the foot and lower leg was determined by the calf raise test. The reliability of differences in indicators was considered significant at the significance level of p<0.05. Results After the end of the pedagogical experiment, the indicators of children in the control group improved in the Friedland index from 26.93±0.3 to 27.29±0.5 (p>0.05), the strength of the foot and lower leg muscles increased by 7.9% (p>0.05), and the jumping ability and fast strength of the leg muscles increased by only 4.7% (p>0.05). In the experimental group, the Friedland index improved from 26.95±0.4 to 29.13±0.3 (p<0.05), the strength of the foot and lower leg muscles increased by 24.6% (p<0.05), and the jumping ability and fast strength of the leg muscles increased by 10.8% (p<0.05). Conclusion The experimental program proved its effectiveness. If special corrective exercises for the prevention or treatment of flat feet are used during each physical education class for 20 minutes, the results of podometry tests, calf raise and standing long jumps will improve significantly. BJMS, Vol. 24 No. 03 July’25 Page : 898-905